Baloxavir Marboxil in Japanese Pediatric Patients With Influenza: Safety and Clinical and Virologic Outcomes. (20th September 2019) - Hirotsu, Nobuo; Sakaguchi, Hiroki; Sato, Chisako; Ishibashi, Toru; Baba, Keiko; Omoto, Shinya; Shishido, Takao; Tsuchiya, Kenji; Hayden, Frederick G; Uehara, Takeki; Watanabe, Akira
Abstract: Background: We assessed the safety and effectiveness of baloxavir marboxil administration in Japanese children with influenza. Methods: This open-label study administered 1 weight-adjusted dose of baloxavir to 107 children aged 1–11 years with laboratory-confirmed, febrile influenza virus infection of ≤48 hours duration. Results: Adverse events (AEs) were reported in 34.6% of patients, most commonly vomiting (7.5%); no serious AEs or AEs causing discontinuation occurred. The median time to alleviation of influenza illness was 44.6 hours (95% confidence interval, 38.9–62.5 hours), to resolution of fever was 21.4 hours, and to sustained cessation of infectious viral shedding was 24.0 hours. However, viruses with amino acid substitutions in the viral polymerase acidic protein at position I38 (PA/I38T/M) emerged in 18 of 77 (23.4%) patients. Emergence was associated with longer infectious virus detectability (median time, 180.0 hours) and time to illness alleviation (median, 79.6 vs 42.8 hours in patients without PA/I38T/M-substituted viruses). Among patients with PA/I38T/M-substituted virus emergence, those with baseline hemagglutinin inhibition (HAI) antibody titer <40 experienced delay in time to illness alleviation (median, 85.4 vs 56.0 hours in patients with higher baseline HAI antibody titer). Conclusions: A single, oral dose of baloxavir marboxil was well tolerated and rapidly reduced viral titers, but the common emergence of PA/I38T/M-substituted viruses warrants consideration of alternative dosing regimens in young children. Clinical Trials Registration: Japan Pharmaceutical Information Center Clinical Trials Information (Japic CTI-163417). Abstract : A single, oral dose of baloxavir marboxil was well tolerated and rapidly reduced viral titers, but the common emergence of PA/I38T/M-substituted viruses warrants consideration of alternative dosing regimens in young children.